Uji In Vitro Gabungan Ekstrak Boesenbergia pandurata, Solanum ferox, Zingimber zerumbet terhadap Bakteri Patogen pada Ikan Nila (IN VITRO TEST OF CONCOCTION PLANT EXTRACTS OF BOESENBERGIA PANDURATA, SOLANUM FEROX, ZINGIMBER ZERUMBET - Hardi, Esti Handayani; Saptiani, Gina; Nurkadina, Nurkadina; Kusuma, Irawan Wijaya; Suwinarti, Wiwin (Jurnal Veteriner; Vol 19 No 1 (2018), 2018)
The aim of this study was to evaluate the antibacterial activity of ethanol concoction (mixed extract) of three herbs plants, such as: Boesenbergia pandurata , Solanum ferox and Zingimber zerumbet against Aeromonas hydrophila , Pseudomonas sp. and both bacteria. The Plant extracts were obtained by using ethanol and the concentration of the extract was 600 mgL-1 of B. pandurata , 900 mgL-1 of S. ferox and 200 mgL-1 of Z. zerumbet . The inhibition zone was measured after 6, 12, 18, 24 h incubation at 30o C. The ratios of concoction S. ferox and B. pandurata (for 100 mL solution) were 90:10; 80:20; 70:30; 60:40; 50:50; 40:60; 30:70; 20:80; 10:90. The same ratios were made on the concoction of S. ferox and Z. zerumbet . The concoctions of S. ferox and B. pandurata in the ratio of 50:50 and 60:40, and the concoction of S. ferox and Z. Zerumbet with ratio 60:40 had higher antibacterial activity against A. hydrophila single isolate compared to the other concoctions. Furthermore, the concoction extract of S. ferox and B. pandurate 50:50 and the combined of S. ferox and Z. zerumbet ratio 50:50 and 90:10 were the best combination to inhibit the growth of a single bacterium Pseudomonas sp. The combined S. ferox and B. pandurata ratio 50:50; 10:90 and S. ferox mixed with Z. zerumbet ratio 50:50 and 40:60 were the best combination against the combined bacteria between A. hydrophila and Pseudomonas sp. The conclusion of this research was the combined extract of S. ferox and B. pandurata and S. ferox with Z. zerumbet are effective to suppress the growth of single or combination of A. hydropila and Pseudomonas sp.